Nenbutsu Orthodoxies in Medieval Japan - Proffitt, Aaron P. (Japanese journal of religious studies, 2020)
New approaches to Buddhist doctrine and practice flourished within and across diverse lineages and sub-lineages in early medieval Japan. The early-modern and modern sectarianization of Japanese Buddhism, however, has tended to obscure the complex ways that the very idea of orthodoxy functioned in this fluid medieval environment. In this article, I explore attempts to account for the diversity of views regarding] nenbutsu orthodoxy in treatises composed by scholars monks affiliated with Mt. Kōya and Mt. Hiei. In particular, this article contextualizes how these monks constructed the idea of an esoteric nenbutsu by drawing upon earlier taxonomies developed in the Tendai school as well as the East Asian esoteric Buddhist corpus. Ultimately, this study concludes that the esoteric nenbutsu was not the provenance of a particular school or sect, but rather served as a polemical construct designed to subsume the diversity of approaches to nenbutsu praxis as monks in diverse lineages competed with one another to define esoteric Buddhism in the early medieval context.